STUDY OF THE RELATIONSHIP BETWEEN GENETIC FACTORS AND THE REPRODUCTIVE HISTORY OF THE MOTHER IN EMBRYO DEATH - Asrankulova Diloram Bakhtiyorovna; Asrankulova Saida Kahramonjon kizi; Akhmadzhonova Gulnoza Murodovna (Galaxy International Interdisciplinary Research Journal, 2024)
Global scientists recognize that increased risk of fetal death, especially spontaneous abortion, increasing maternal age, previous spontaneous abortions, and multigravid status are favorable risk factors for spontaneous abortion in subsequent pregnancies. Because these factors are interrelated, maternal age, given a woman’s reproductive history, may influence embryonic mortality.